Pengaruh Motivasi Kerja dan Kompetensi Terhadap Kinerja Pegawai Pada Dinas Perumahan dan Kawasan Permukiman Provinsi Sumatera Selatan (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The formulation of the problem in this study is that there is a phenomenon that occurs in the field that the housing and settlement area services of South Sumatra Province have problems such as minimal employee motivation due to demands to fulfill their rights and obligations as state civil servants, as well as a decreased level of enthusiasm so that it becomes an obstacle for the realization of the performance process in completing the work given. This study aims to determine the motivation and competence of the employees of the Department of Housing and Residential Areas of South Sumatra Province. Sampling of 53 respondents in this study using simple random sampling technique. The data analysis technique used multiple linear analysis with the help of the IBM SPSS 22 program. The results obtained both partially and simultaneously that work motivation and competence have a positive and significant effect on employee performance in the Housing and Settlement Area Office of South Sumatra Province.